A New, Potent, and Placenta-Permeable Macrolide Antibiotic, Solithromycin, for the Prevention and Treatment of Bacterial Infections in Pregnancy - Keelan, Jeffrey A.; Payne, Matthew S.; Kemp, Matthew W.; Ireland, Demelza J.; Newnham, John P. (Frontiers in Immunology, 2016)
Intrauterine infection–inflammation is a major cause of early preterm birth and subsequent neonatal mortality and acute or long-term morbidity. Antibiotics can be administered in pregnancy to prevent preterm birth either prophylactically to women at high risk for preterm delivery, or to women with diagnosed intrauterine infection, prelabor rupture of membranes, or in suspected preterm labor. The therapeutic goals of each of these scenarios are different, with different pharmacological considerations, although effective antimicrobial therapy is an essential requirement. An ideal antibiotic for these clinical indications would be (a) one that is easily administered and orally bioactive, (b) has a favorable adverse effect profile (devoid of reproductive toxicity or teratogenicity), (c) is effective against the wide range of microorganisms known to be commonly associated with intra-amniotic infection, (d) provides effective antimicrobial protection within both the fetal and amniotic compartments after maternal delivery, (e) has anti-inflammatory properties, and (f) is effective against antibiotic-resistant microorganisms. Here, we review the evidence from clinical, animal, and ex vivo/in vitro studies that demonstrate that a new macrolide-derived antibiotic – solithromycin – has all of these properties and, hence, may be an ideal antibiotic for the treatment and prevention of intrauterine infection-related pregnancy complications. While this evidence is extremely encouraging, it is still preliminary. A number of key studies need to be completed before solithromycin’s true potential for use in pregnancy can be ascertained.